Impact of Renewable Resources on Economic Development in Rural Areas - Zhong, Qi (International Journal of Social Sciences and Public Administration, 2024)
With the transformation of global energy structure and the concept of sustainable development, many countries have gradually become the key factor to promote social and economic development in rural areas. Rural areas, as a potential treasure land for the development of renewable resources, are rich in solar energy, wind energy, biomass energy and other resources. The rational development and utilization of these resources can bring many benefits to rural areas. Therefore, the government clearly put forward the strategic development goal of renewable energy, technology innovation and policy support, the key to promote renewable resource utilization, to promote the construction of the rural agriculture and wisdom. However, in the process of rural energy transformation, there are also challenges such as scattered distribution of residents, limited consumption power, and insufficient awareness of environmental protection. Based on this, this paper focuses on how these resource cities can be used to transform into economic advantages in rural areas.